Why Do Birds Flock? A Role for Opioids in the Reinforcement of Gregarious Social Interactions - Riters, Lauren V.; Kelm-Nelson, Cynthia A.; Spool, Jeremy A. (Frontiers in Physiology, 2019)
The formation of social groups provides safety and opportunities for individuals to develop and practice important social skills. However, joining a social group does not result in any form of obvious, immediate reinforcement (e.g., it does not result in immediate copulation or a food reward), and individuals often remain in social groups despite agonistic responses from conspecifics. Much is known about neural and endocrine mechanisms underlying the motivation to perform mate- or offspring-directed behaviors. In contrast, relatively little is known about mechanisms underlying affiliative behaviors outside of these primary reproductive contexts. Studies on flocking behavior in songbirds are beginning to fill this knowledge gap. Here we review behavioral evidence that supports the hypothesis that non-sexual affiliative, flocking behaviors are both (1) rewarded by positive social interactions with conspecifics, and (2) reinforced because affiliative contact reduces a negative affective state caused by social isolation. We provide evidence from studies in European starlings, Sturnus vulgaris, that mu opioid receptors in the medial preoptic nucleus (mPOA) play a central role in both reward and the reduction of a negative affective state induced by social interactions in flocks, and discuss potential roles for nonapeptide/opioid interactions and steroid hormones. Finally, we develop the case that non-sexual affiliative social behaviors may be modified by two complementary output pathways from mPOA, with a projection from mPOA to the periaqueductal gray integrating information during social interactions that reduces negative affect and a projection from mPOA to the ventral tegmental area integrating information leading to social approach and reward.